Modeling deformation twinning in BCC transition metals - Faisal, Anik H. M., author; Weinberger, Christopher, advisor; Radford, Donald, committee member; Ma, Kaka, committee member; Heyliger, Paul, committee member (Colorado State University. Libraries, 2023)
Deformation twinning is one of the important deformation mechanisms in body centered cubic (BCC) transition metals, especially under low temperature and high strain rate conditions. Plastic deformation via deformation twinning has been studied for decades both experimentally and computationally however, atomic level insights such as critical nuclei size, their local atomic structures and energetics which are important parameters in modeling twin nucleation has been lacking. In this work, deformation twins in BCC transition metals and their atomic level structures and energetics have been rigorously studied to reveal the full atomic level details of twin nucleation and propagation. As such, critical thickness of deformation twins in BCC transition metals have been a topic of debate with many computational and experimental studies accepting a three-layer twin thickness based on nucleation from a screw dislocation without proof whereas recent in-situ experiments suggest six-layer thick twin nuclei observed via High resolution transmission electron microscopy (HRTEM). In this study, we have determined the critical twin nuclei thickness in these metals using atomistic simulations to examine atomic structure and energetics of deformation twins under both zero and nonzero finite pure shear stresses. Our study reveals that twins in group VB BCC transition metals nucleate as two-layer thick nuclei under stress as opposed to the three-layer thick twin nuclei under zero stress. For group VIB BCC transition metals, for both zero and nonzero stresses, the critical twin nuclei thickness is two layer near reflection. As the twins grow and stress is relieved, twins under finite stresses adopt configurations that are much closer to the zero stress stability predictions. In addition to nucleation, growth of mechanisms of twins are explored and computational insights into the growth of twins in Tungsten bicrystals explaining multi-layer growth as opposed to layer-by-layer growth associated with small barriers. Free-end string simulations were used to investigate energy barrier associated with homogeneous twin nucleation using embedded atom method (EAM) potentials. Since homogeneous twin nucleation occurs near the ideal strengths of the material described by the potentials, energy barrier calculations were not possible for all BCC transition metals as some available potentials break down under large stresses. Moreover, density functional theory (DFT) simulations are known to be more accurate in describing atomic bonding but direct nucleation simulations in bulk crystals is prohibitively expensive. Hence, existing dislocation nucleation models are thoroughly analyzed to examine the behavior of these models near ideal strength of the material because spontaneous nucleation of dislocations occurs at high stresses. From there, a robust homogeneous twin nucleation model that includes elastic interaction among the twinning dislocation loops is developed which is able to replicate energy barrier data from free-end string simulations for multiple interatomic potentials. This model takes atomistic simulation inputs such as the concurrent twinning generalized stacking fault (GSF) energy curves and corresponding burgers vector of the twinning dislocations to compute the energy barriers as a function of applied stress. This model can be useful in modeling homogeneous twin nucleation all BCC transition metals and has the potential advantage of using DFT simulation inputs for accurate description of atomic bonding within the twin nuclei. Finally, nucleation stresses for twinning in bulk crystals have been studied to investigate whether the formation of twinning in experimental studies were initiated by homogeneous nucleation. Upper and lower bounds of stress values required for homogeneous twin nucleation has been computed and a semi-empirical model has been developed to predict homogeneous twin nucleation stresses as a function of temperature and strain rate. This analysis shows that reported critical resolved shear stress (CRSS) values in experimental studies are not associated with homogeneous twin nucleation despite some modeling studies claiming otherwise.
Keywords: continuum mechanics; mechanical properties; plastic deformation; deformation twinning; atomistic simulations; nucleation and growth